Creating 3D terrain/urban from Google earth - Lim, Eugene Keng Siang. (2012)
There is an increasingly demand of using realistic 3D terrain as a common tool for communication, education and urban planning. Traditional modeling method of 3D terrain was time-consuming as it required numerous works to create 3D models using laser scanner data. The modeling tool also required high user’s expertise. 3D environment tool such as Google Earth allows users to navigate and obtain geographic terrain information for any part of the world. With the aid of Google Earth application program (API), a software prototype had being developed in Java to generate 3D terrain efficiently using the geographic terrain information. This report explains the enhancement of the interactivity of the software prototype, integration of many functions including using of Swing to enable undo/redo state in building editor, removing of Google Earth Logo during texture mapping, perform multiple buildings modeling in the building editor, export result as VRML format files, VRML viewer and Zooming of model in the building editor.